MANUSCRIPT BOOK AS A SOURCE OF RESEARCH: HISTORY OF A CODEX IN THE GDL - CICĖNIENĖ, RIMA (Knygotyra, 2014)
When conducting research, it is important for a historian to examine not only the event or object of interest, but all of the decisive circumstances, chronology, places and persons involved as well. It is in order to attain this goal, that sources of information are collected, analysed and interpreted. Humanitarian disciplines tend to research manuscripts as material artefacts, literary texts or means of cultural transactions. However, it is not common in Lithuania for manuscripts to be used as a source of research. A manuscript, copied in the 15th century GDL, was chosen to illustrate this statement. The book was sometime later divided into two parts that are now stored separately in the National Library of Russia and the Wroblewski Library of the Lithuanian Academy of Sciences. This article was written in order to determine the history of manuscript book Collection of Sermons by Isaac of Nineveh, while at the same time presenting ways to use manuscripts as a legitimate source in cultural and historical research. The study was carried out by using codicological and comparative methods as well as analysis of literature and archival sources. Detailed codicological descriptions of both books were written. The hypothesis, that the two codices, which were copied by hand at the start of 15th century, are two parts of one exemplar, was proven true on the basis of the results that were obtained. The article contains information about the historical and cultural contexts surrounding the birth of this book. The history of how the codex was copied and stored is reconstructed and the persons involved in the process are discussed in the article as well. The complex research of the dated exemplar reveals that the manuscript book as well as its separate structural elements and the materials it was made of can be used as a source of information for research in at least several scientific disciplines such as history, literature and bibliography. The codex itself could be considered as an interdisciplinary source of research. The postscript, which remained in the codex, contains two colophons and the Praise for Witold. This text is published at the end of the article in its original orthography.